162 Simultaneous measurement of calcium transients and electrical activity in murine cardiac tissue – a novel system for the study of cardiac arrhythmia. (6th June 2015) - Yeoh, Alastair; Finlay, Malcolm; Anderson, Naomi; Harmer, Stephen; Tinker, Andrew
Abstract : Introduction: Cardiac arrhythmia is a major source of morbidity and mortality. More effective diagnosis and treatment requires a deeper understanding of the underlying pathophysiology of arrhythmia. Aberrant calcium handling is implicated in arrhythmogenesis. This study describes the development of a novel system to simultaneously measure calcium and electrophysiology at the tissue level. Existing research primarily employs single cell or whole heart models, but there is a translational gap between these levels of study which this model is intended to bridge. Methods: A combined calcium fluorescence and solid-state electrical recording system was set up on an inverted microscope. Samples of murine tissue were loaded with a fluorescent calcium indicator dye (Fluo-4 AM). Intracellular calcium transients (elicited by electrical stimulation via external electrodes) were recorded by a CMOS digital camera, which measured emission light from samples excited with a narrow wavelength LED. The validity of this calcium imaging system was assessed by measuring the effects of decreased cycle length and pharmacological agents on calcium transients. Electrical and fluorescence data were then obtained simultaneously. Electrical data were recorded by contact electrodes in a multi-electrode array. Results: Tissue was successfully loaded with fluorescent dye and calcium transients (observed as increases in green fluorescence) elicited by electrical stimulation were recorded. Calcium transient height and duration decreased by 19% (p < 0.001) and 16 ms (95% CI 13–20) respectively when coupling intervals were reduced from 400 ms to 200 ms (n = 5). Isoprenaline 100 nm reduced calcium transient length by 10 ms (95% CI 4.8–16) (n = 5). Increasing concentrations of nifedipine showed a dose-dependent decrease in calcium transient size (n = 1). Calcium fluorescence transients were successfully measured in tandem with electrical activity. Conclusion: The current study describes the successful development of a calcium fluorescence imaging system and its integration into a multi-electrode array recording system. This experimental paradigm provides a novel multi-parametric tool for the study of arrhythmia in cardiac tissue.